Pengaruh Model Learning Cycle 8E Terhadap Pemahaman Konseptual Siswa Kelas XI Pada Materi Hidrolisis Garam: Pengaruh Model Learning Cycle 8E Terhadap Pemahaman Konseptual Siswa Kelas XI Pada Materi Hidrolisis Garam - Elma Suryani; Maria Paristiowati; Dini Delfiana (Jurnal Riset Pendidikan Kimia (JRPK), 2026)
Students’ conceptual understanding remains low in chemistry, particularly in the topic of salt hydrolysis. This study aims to determine the effect of the 8E learning cycle model on the conceptual understanding of 11th-grade students in the subject of salt hydrolysis. This research is a quasi-experimental study with a non-equivalent pre-test/post-test control group design. Pre-test and post-test were administered to collect data on students’ conceptual understanding. The sample consist of 68 students, including 34 students in the experimental class were taught using the 8E learning cycle model, and 34 students in the control class were taught using the 5M model. The result of N-gain of the experimental class was 0.642, while the control class had an average of 0.44. The average N-gain of both classes is medium category, although the N-gain of the experimental class was higher. Based on the Mann-Whitney U test, a significant difference was found between the post-test conceptual understanding results of the control class and the experimental class. Therefore, it can be concluded that the implementation of the 8E Learning Cycle has an impact on the conceptual understanding of the salt hydrolysis topic. These finding indicate that the 8E Learning Cycle is effective in improving students’ conceptual understanding in the topic of salt hydrolisis.